Monstrosity, Anxiety and the Real: Representations of the Victorian Metropolis in David Lynch's The Elephant Man - Torsten Lange (Opticon1826, 2007)
The following paper will offer an interpretation of David Lynch's film The Elephant Man, and its representations of late-Victorian London as a monstrous and deformed body. Besides tracing these themes in a discussion of exemplary scenes of the film, I wish to illuminate how underlying notions of monstrosity in the writings of Victorian urban explorers and reformers contributed to ideas and anxieties about the body and domesticity, and helped to promote the image of a clean, sanitized and civilized city. I will make use of a range of theoretical and historical approaches developed within and inbetween a variety of disciplines such as anthropology, geography and architectural history, as well as literary studies, film theory and psychoanalysis, and, in so doing, aim to complicate the image of the monstrous metropolis.
Keywords: psychoanalysis; deformity